South Africa: Psychology's dilemma of multiple discourses - Kottler, Amanda (PINS-Psychology in Society, 2025)
This paper examines, on a political and a psychological level, two central and contrasting South African discourses. Both are particularly evident in the anthropological literature of the 1980s, especially that which focuses on the issue of professionalization of "African" medicine (Kottler, 1988). This paper identifies the similarities discourse as the dominant anti-apartheid discourse and notes that it takes little account of the psychological factors which are identified in the differences discourse. The similarities discourse therefore leaves the differences discourse in an awkward space, suggesting as it does that those who are positioned within it aid the Government in its quest for separate development and inequality. This paper argues however, that the similarities discourse is also politically untenable, leaving out, as it does, important psychological considerations. Since the differences discourse is frequently regarded as the progressive political stance outside South Africa important contradictions are apparent and the dilemma of difference is introduced. This paper attempts to tease out some of these contradictions and argues for further psychologically informed research in this direction.